KEMAMPUAN MENULIS PUISI SISWA KELAS VA SD NEGERI 44 KOTA BENGKULU - Riska Dwi Handayani; Pebrian Tarmizi; Yuli Amaliyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the poetry writing skills of Grade VA students at SD Negeri 44 Kota Bengkulu. The method used in this research is descriptive qualitative with a literature study approach. The subjects of this study were 20 students from Grade VA. Data were collected through poetry writing assignments with the theme of natural beauty and analyzed based on the elements of poetry, namely: diction, imagery, concrete words, figurative language, versification, and typography. The research instrument used was a table for analyzing students’ poems. The data analysis process was carried out through several stages, namely: data collection, data condensation, data display, and conclusion drawing/verification. Based on the results, students consistently used diction related to nature, although it remained simple. Imagery was dominated by visual imagery, while auditory and tactile imagery were not yet evenly developed. All students used concrete words to describe real natural objects; however, the use of figurative language, especially personification, was not evenly distributed across all works. The rhyme and rhythm of the poems tended to be free and not consciously structured, while the typography generally used lines and stanzas, although some works still resembled prose. A total of 16 students used all six elements of poetry completely. Meanwhile, four students did not use figurative language, resulting in poems that were still directly descriptive. It can be concluded that the students’ poetry writing skills are at an early to developing stage, characterized by the use of simple diction and concrete words, the dominance of visual imagery, and the uneven use of figurative language and rhyme.